Implementasi Algoritma Advanced Encryption Standard dalam Pengamanan Data Penjualan Ramayana Department Store - Sunil Setti; Indra Gunawan; Bahrudi Efendi Damanik; Sumarno Sumarno; Ika Okta Kirana (JURIKOM (Jurnal Riset Komputer), 2020)
Ramayana Department Store is one of the companies engaged in the business of retail supermarket. The company uses computer science technology applied in servicing activities, particularly in the sales data storage. Sales data is the information generated from sales transaction activities that obtained by the company through marketing activities to make profits. The use of computers in storing sales data is used to improve data security so that the valuable information can be confidentiality guaranteed. To avoid data theft and data manipulation,we need to implement a security system. Cryptography is a science that uses mathematical equations to keep the information secure such as data confidentiality, data validity, data integrity, and data authentication. A method that can be used to secure messages / information is the Advanced Encryption Standard (AES). The application of the AES cryptography algorithm in securing the sales data of the Ramayana Department Store shows that the algorithm can make encryption that cannot be read or understood by humans and make decryption that exactly same with the initial plaintext input. The difference of the key and the size of a file also affecting the time required to perform the encryption and decryption process